Impact of iron hydroxide (III) on level of postoperative anemia in patients with combined mitral and aortal heart failures - B. M. Gumenyuk (Клінічна хірургія)
Objective. To investigate a combined impact of iron hydroxide (III) on the anemia level after prosthesis of mitral and aortal valves in accordance to the blood-preserving technology in conditions of artificial blood circulation.